The Influence of Organizational Culture and Job Training on Employee Performance Through Job Satisfaction as a Mediating Variable - Azhari, Muhammad Hanafi; Soelistya, Djoko; Desembrianita, Eva (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
The development of the business world is very fast, as is the case with the food industry. This dynamic development means that companies are required to provide optimal results in order to have good competitiveness. The aim of this research is to examine the influence of organizational culture and job training on employee performance through job satisfaction as a mediating variable. The research method uses a quantitative approach through questionnaires distributed to employees in the packing oil department in various oil and gas industry companies. The population and sample used were 141 respondents. The results of this research show that organizational culture has a positive and significant direct influence on employee performance, job training has a positive and significant direct influence on employee performance, organizational culture has a positive and significant direct influence on job satisfaction, job training has a direct influence. positive and significant on employee performance, job satisfaction has a positive and significant direct influence on employee performance, while the indirect influence is that organizational culture has a positive and significant direct influence on employee performance through job satisfaction as mediation, and job satisfaction functions as partial mediation , and job training have a positive and significant direct influence on employee performance through job satisfaction as mediation, and job satisfaction functions as partial mediation. Therefore, increase job training with external parties and increase job satisfaction by creating programs for character development, so that employee performance can increase.